Examining geopolitical risks and crime relationship : insights from Europe - Er, Selahattin Tolga (My University, 2022)
Daha önce yapılan araştırmalar, silahlı çatışma, terör ve uluslararası ilişkilerde barışçıl seyri bozan uluslararası anlaşmazlıklardan kaynaklanan jeopolitik tehditlerin, ekonomik eşitsizliğe ve ekonomik büyümede bozulmaya neden olarak toplum ve ekonomi üzerinde ciddi sonuçlar doğurduğunu göstermiştir. Bu çalışmada ise, jeopolitik risklerin ekonomik sonuçlarının yasal yollardan elde edilen faydayı baskıladığı, normlarda kırılma yarattığı ve toplumun savunmasız kesimleri üzerinde gerilime neden olduğu vurgulanarak, jeopolitik riskler ile mal varlığına karşı işlenen suçların ilişkisi 13 Avrupa ülkesi bağlamında 1995-2016 yılları için analiz edilmiştir. Çalışmanın bulguları, jeopolitik risklerdeki artış ve azalışların mal varlığına karşı işlenen yağma ve hırsızlık suçlarındaki değişimlerle aynı yönde ilişkide olduğunu göstermektedir. Araştırmanın sonuçları 13 Avrupa ülkesi örnekleminin yanı sıra 9 ülkeyi içeren Kuzey ve Batı Avrupa kümesine karşı sağlamdır.

Previous research has shown that increasing geopolitical threats and events that arise from armed conflicts, terror, and conflicts among states that disrupt the peaceful course of international relations have severe consequences on society and the economy by causing economic inequality and harming economic growth. Arguing that the economic and social consequences of geopolitical risks lead to diminishing expected utility from legal work, disruption in the norms of the society, and increasing strain on vulnerable people of the society, this study analyzed the association between geopolitical risks and acquisitive crimes in the context of Europe with a sample of 13 countries. The findings revealed that the changes in geopolitical risks and acquisitive crimes, namely, robbery and theft, are positively associated from 1995 to 2016. The study results are robust to the sample of 13 European countries and the cluster of Northern and Western Europe, with 9 countries.
Keywords: European Sourcebook; Finance; Geopolitical Risks; GPR Index; GPR Index Crime; Hırsızlık; Jeopolitik Risk; Maliye; Robbery; Suç; Theft; Yağma